IMPLEMENTATION OF FOGGING AS AN EFFORT TO ERADICATE MOSQUITO THE CAUSE OF DENTAL FEVER IN SOUTH WEST ACEH DISTRICT - Khairina; Jun Musnadi Is; Darmawan; Fikri Faidul Jihad (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Fogging or fogging is the process of spraying mosquitoes, especially pesticides, to kill carriers (vectors) of dengue hemorrhagic fever (DHF). The purpose of this study was to find out the implementation of fogging as an effort to eradicate mosquitoes that cause dengue fever in Aceh Barat Daya district. The method used by researchers in this research is qualitative and can be called a natural research method because it was carried out in a natural environment. The results showed that the implementation of fogging as an effort to eradicate mosquitoes that cause dengue fever in Aceh Barat Daya District has not been effective in reducing the number of DBB sufferers due to inadequate socialization of DHF control.